Serum Biochemical Profile of Nile Tilapias (Oreochromis niloticus) Bred in Net Cages during Summer and Winter - Rodrigues, Gustavo Moya; Nascimento, Fernanda Gatti de Oliveira; Bizare, Amanda; Oliveira, Wilson Junior; Guimarães, Ednaldo Carvalho; Mundim, Antonio Vicente (Acta Scientiae Veterinariae, 2018)
Background: The growth of fish farming in Brazil has been noticeable over the past few years, and the Nile tilapia (Oreochromis niloticus) is the most bred species in the country. Studies on the physiology of these animals are necessary so that the production continues to grow and to improve its rates. However, very discrepant data are still found in the area of blood biochemistry. The aim of this study was to evaluate the physiological variations in serum concentrations of proteins, metabolites, electrolytes and serum enzymes in Nile tilapias bred in net cages in Cachoeira Dourada, state of Minas Gerais, Brazil, during summer and winter. Materials, Methods & Results: During the year of 2016, samples from 100 Nile tilapias were collected during summer (January and February) and samples from 100 Nile tilapias were also collected during winter (July and August). Only one blood sample was collected by caudal venipuncture of each fish, just before the slaughter, always in the morning. The serum samples obtained were then analyzed for serum concentrations of proteins, metabolites, electrolytes, lipids and serum enzymes. Serum concentrations of total proteins, globulins, triglycerides, high density lipoprotein (HDL), alkaline phosphatase, sodium and chloride were significantly higher during winter in comparison to summer, while the serum concentration of uric acid was significantly lower during winter in comparison to summer. Discussion: Due to the lower temperature of water during winter, tilapias reduced food intake and became more susceptible to diseases, which led to an increase in circulating globulins. In that same season, there was an increase in serum concentrations of sodium and chloride as a result of adding sodium chloride to the water in order to stimulate mucus secretion on the fishes’ skin and gills to prevent pathologies. Triglycerides, HDL, and uric acid are considered indicators of nutritional status of animals. The increase in serum concentrations of triglycerides and HDL indicates that tilapias are mobilizing energy reserves, however, when the increase in serum concentrations of uric acid is observed, it is fair to assume there has been an increase in food intake, raising protein catabolism. The increase of serum concentration in alkaline phosphatase is caused by the presence of multiple forms of enzymes that are induced by the action of endogenous corticosteroids, which are produced as a result of the stress suffered by tilapias during the fishing process and during winter, when the water temperature is lower than the ideal for this species. It can be concluded that the season has influence on some serum biochemical constituents of Nile tilapias bred in net cages, and that the predominant variations happen during winter due to immunity decline and during summer due to the increase in food intake and, consequently, in the metabolism of tilapias.